Hard winter - Johnstone, William W. (Montana Yesterday & Today, 2024)
Two families. Two dynasties. Two centuries. A saga of Montana. Bestselling authors William W. Johnstone and J.A. Johnstone return to Cutthroat County in their Montana series, following the Maddox and Drew families from the time they struggled to plant their roots in the 1800s to the twenty-first century trials they endure to maintain their legacies.